A novel submersible-mounted sediment pressure-retaining sampler at full ocean depth - He, Shudong; Qiu, Sawei; Tang, Wenbo; Peng, Youduo; Jin, Yongping (Frontiers in Marine Science, 2023)
High-efficiency pressure-retaining sampling technology for obtaining seabed sediments is required for studying marine geological history, the survival principles of marine microorganisms, and the evolution of earth life. In this paper, a novel submersible-mounted sampler capable of collecting pressure-retained samples at a full ocean depth is designed. The structure scheme is first presented, including the sampling unit, pressure-retaining unit, and pressure-compensation unit. The sampling kinematics model is then established, and the influences of pressing velocity, and the length and inner diameter of pressure pipe on the pressing force of the mechanical arm are determined, providing important guidance for the design of the sealing structure. The maximum working depth of the sampler is 11,000 m, the coring diameter of the sampler is 54 mm, the maximum coring depth is 500 mm, and obtained samples can keep close to in-situ pressures. The sampler can be mounted on a submersible and operated using a single mechanical arm. During cruise TS-21 from August to October 2021, the sampler was deployed 4 times at depth of 7700 m in the West Philippine Basin, and the high pressure sediment samples were successfully collected. The pressure change of the samples remained within ±6%, which verified the rationality of the design and the feasibility of this novel submersible-mounted pressure-retaining sampler.